2018
DOI: 10.1111/ijlh.12909
|View full text |Cite
|
Sign up to set email alerts
|

An integrated flow cytometry analysis of 286 mature B cell neoplasms identifies CD13 as a useful marker for diagnostic subtyping

Abstract: CD13 expression is present more often in LPL- and FMC7-positive CLL/SLL than other mature B cell lymphoma subtypes and absent in cases of FL and may be a useful feature for diagnostic subtyping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Although specificity for LPL/WM cells was higher in CD13 than VS38 (Table 7), CD13-positive B cells were only part of whole LPL/WM cells. In previous reports, CD13 stains LPL/WM cells with high specificity; however, positive rates were low (Lau et al, 2018;Raimbault et al, 2019), consistently with our data. We believe that VS38-gating can simultaneously allow capturing most LPL/WM cells while narrowing down a subset of LPL/WM cells from a heterogeneous background of mostly normal B cells (Table 7 and Figure 5).…”
Section: Evaluation Of Immunophenotype In Lpl/wm Cellssupporting
confidence: 92%
See 1 more Smart Citation
“…Although specificity for LPL/WM cells was higher in CD13 than VS38 (Table 7), CD13-positive B cells were only part of whole LPL/WM cells. In previous reports, CD13 stains LPL/WM cells with high specificity; however, positive rates were low (Lau et al, 2018;Raimbault et al, 2019), consistently with our data. We believe that VS38-gating can simultaneously allow capturing most LPL/WM cells while narrowing down a subset of LPL/WM cells from a heterogeneous background of mostly normal B cells (Table 7 and Figure 5).…”
Section: Evaluation Of Immunophenotype In Lpl/wm Cellssupporting
confidence: 92%
“…Lymphoma cells in the bone marrow are important to identify at the time of LPL/WM diagnosis, and the presence of an MYD88 L265P mutation is especially useful for determining this (Jiménez et al, 2013;Varettoni et al, 2013;Xu et al, 2013). Lymphoma cells express CD13, CD25, and CD27 in patients with LPL/WM (Lau et al, 2018;Paiva et al, 2014). However, varying positive rates and expression levels of Abbreviations: BCL, B cell lymphoma; CLL, chronic lymphocytic leukemia; FL, follicular lymphoma; HCL-v, hairy cell leukemia-variant; LPL, lymphoplasmacytic lymphoma; MCL, mantle cell lymphoma; SMZL, splenic marginal zone lymphoma; WM, Waldenström macroglobulinemia.…”
mentioning
confidence: 99%
“…Aminopeptidases are involved in many human disorders, including autoimmune diseases and cancer. For example, aminopeptidase N (ANPEP alias CD13) is abnormally expressed in AML, B-cell acute lymphoblastic leukemia, and chronic lymphoblastic leukemia, where it may be used as a diagnostic or prognostic marker [6][7][8]. ANPEP is also expressed in a subset of Waldenström macroglobulinemia, MM, and plasma cell leukemias [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Raponi et al reported CD22 expression among different subtypes of ALL as 83% of Pro-B, 96.4% of common B cell, 91.9% of Pre-B and 100% of the mature B cell ALL [70]. In mature B cell lymphoma, its expression has been reported as 95% in chronic lymphocytic leukemia, 89% in diffuse large B-cell lymphoma, 98% in follicular lymphoma, 96% in lymphoplasmacytic lymphoma and 100% in hairy cell, mantle cell, marginal zone, splenic marginal zone lymphomas and monoclonal B-lymphocytosis [71]. Hence CD22 can serve as a good target for therapy of B cell malignancies.…”
Section: Cd22 Positivity In Lymphoid Malignanciesmentioning
confidence: 99%